Literasi Keuangan Digital sebagai Determinan Perilaku Menabung Generasi Z di Indonesia - Agatha Pricillia Sekar Tamtomo; Mutia Ulfa; Graceilla Kristia Seraphim Budiono; Ahmad Aufar Ribhi; Muhammad Anwar Fauzi (Economic Reviews Journal, 2026)
This study aims to examine the influence of digital financial literacy on the saving behavior of Generation Z in Indonesia based on findings from previous studies. A qualitative approach was employed through a literature review of eleven relevant scientific articles discussing digital financial literacy and saving behavior, particularly among Generation Z and university students. The results indicate that the majority of studies report a positive and significant relationship between digital financial literacy and saving behavior. This suggests that individuals with higher levels of digital financial literacy tend to have better financial management skills and demonstrate stronger saving habits. However, several studies present contrasting findings. Some research revealed that financial literacy does not have a significant effect on students’ saving behavior or saving intentions. These findings imply that financial knowledge alone may not be sufficient to encourage consistent saving practices, as saving behavior may also be influenced by internal factors such as self-discipline and personal financial control. Based on the review of the selected articles, it can be concluded that digital financial literacy generally has a positive and significant influence on the saving behavior of Generation Z in Indonesia, although its impact may vary depending on individual characteristics.